Estimation of carbon stock variation between the two management zones of the Yayo Biosphere Reserve: Southwestern Ethiopia - Tokuma Urgessa; Dereje Mosissa (CV. Literasi Indonesia, 2026)
Forests are powerful natural systems that capture and store carbon, holding amounts comparable to what is found in the atmosphere. Their above- and below-ground biomass (AGB and BGB) form the largest carbon pools, responding quickly to disturbances and serving as key indicators of ecosystem health. Measuring these pools is vital for monitoring forest stability. This study explored woody plant diversity and carbon stocks in the Yayo Biosphere Reserve, focusing on the Transition and Buffer zones. Data came from 80 systematically placed plots (25×25m, 500m apart), where tree height and diameter (DBH ≥ 2.5cm) were recorded, alongside soil samples at 0–15cm and 15–30cm depths. Using allometric equations, both AGB and BGB were estimated. Results documented 5,290 trees across 65 species and 41 families. Biomass analysis showed significant differences in AGB between zones (257.04±1.75 t ha⁻¹ vs. 138.29±1.31 t ha⁻¹), while BGB differences were negligible. Soil organic carbon varied significantly at 0–15cm but not deeper. Findings reveal that human disturbances affect the buffer zone as much as the transition zone, highlighting the urgent need for stronger monitoring and protection to safeguard forest integrity.